The Role of Stakeholder Engagement in Enhancing Educational Outcomes in South Africa - John Smith; Lara Williams (JMPI: Jurnal Manajemen, Pendidikan dan Pemikiran Islam, 2024)
This study aims to explore the importance of communication between schools and parents, community support, and stakeholder engagement in improving educational outcomes. The method used in this research is a qualitative approach with in-depth interviews and participatory observations. Data were collected from teachers, parents, students, and community members to gain a comprehensive understanding of the dynamics of engagement in education. The results of the study indicate that effective communication between schools and parents significantly contributes to parental involvement, which has a positive impact on student motivation and achievement. Community support, through various activities that involve the community, also strengthens the relationship between schools and families, creating a more supportive educational environment. Despite challenges such as time constraints and opportunities for participation, the findings of this study suggest that efforts to enhance stakeholder engagement are crucial in achieving better educational goals. This research recommends the development of inclusive communication strategies and programs that provide opportunities for all stakeholders to contribute to the educational process.